The Miracle of Mangrove, Peningkatan Pengetahuan dan Kesadaran Masyarakat Kuri Caddi terhadap Keberadaan Mangrove - Andi Hurul Auni Usman; Meta Dilianti Palimbunga; Basran Nur Basir; Aswar Aswar; Ma’rifa Baharuddin; Ira Taskirawati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The potential natural resources namely mangrove forests and marine ecosystems in the Kuri Hamlet The Caddi Team encouraged the Student Creativity Program (PKM) of Hasanuddin University students in the PKM-M Blue Forest activities to encourage the community to carry out community service activities. The purpose of this activity is to increase public knowledge and awareness about mangrove challenges in the Kuri Caddi Hamlet. Prior to the activity, prior tests were conducted to measure the community's initial ability regarding mangroves. The implementation process teaches how to use lecture, discussion, direct practice, and brainstorming methods. Then to use the evaluation used a post-test to identify increased understanding of community learning. After the Blue-Forest Activity, the community increased their knowledge about mangrove introduction material by 59% from 100%, Awareness of utilization by 63% from 100% and mangrove forest parts by 63% from 100%. So, prior to the activity, PKM-M Blue-Forest carried out based on average knowledge about mangroves was only 26% from 100%. After this activity is carried out, the partner's knowledge increases to 61% from 100%.